Strontium-doped lime catalysts for biodiesel production: activity and stability during soybean oil methanolysis - Dias, Ana Paula Soares (2020)
Biodiesel produced by alcoholysis of vegetable oils is a low carbon fuel, which can replace the fossil diesel in internal combustion engines. CaO is a cheap and environmentally benign material showing interesting catalytic performances in the methanolysis reaction of vegetable oils. However, the reaction rate is slower than the conventional homogeneous-catalyzed by sodium methoxide. In order to improve the catalytic activity, lime catalyst (commercial) was doped with different amounts of strontium. The catalysts, prepared by wet impregnation using aqueous solutions of nitrate salt, were calcined at 575 °C and 800 °C. The physical-chemical characterization of catalysts showed that the doping element had an apparently null effect on the basicity assessed by Hammett indicators. The Ca(OH)2, with weak basicity, formed in the Sr-modified catalysts eventually masked the Sr effect on the basicity. In the tested conditions, all the prepared catalysts were active allowing fatty acid methyl esters’ (FAME) yields higher than 94%. The catalyst stability tests, performed without intermediate reactivation, showed that Sr dopant promoted accelerated decay due to calcium diglyceroxide formation which is leached into the reaction medium. High temperature calcination had a negative effect on the catalyst stability due to the formation of Ca(OH)2. Such undesired effect was prompted by the Sr dopant.